Myelodysplastic syndromes: therapeutic problems and decisions (review) - S. V. Semochkin; T. N. Tolstykh; A. G. Rumyantsev (Онкогематология)
Myelodysplastic syndromes (MDS) are a group of heterogeneous clonal disorders of myeloid hematopoietic stem cells characterized by an ineffective hematopoiesis associated with cytopenias, morphologic dysplasia and a progression to acute myeloid leukemia. The only potentially curative MDS treatment is hematopoietic stem cell transplantation, which is usually not even discussed because most patients with advanced age at diagnosis. Currently only three drugs are approved by US Food and Drug Administration (FDA) and European Medicines Agency for therapy of MDS. For low and intermediate-1 risk MDS del(5q) the novel immunomodulatory drug lenalidomide is asserted, and for intermediate-2 and high risk the two hypomethylating agents (azacitidine, decitabine) are approved. The results of completed clinical trials demonstrating the efficacy and safety of these agents are presented. The new data indicating that the successful future of MDS treatment rests in the combination of multiple treatments modalities to achieve improved clinical outcomes are discussed in this review.